The Relationship Between Temporal Sense and Psychopathologies of College Students with Sensory Impairments: Mediation of Religions - Dai, Yan (Journal of religion and health, 2025)
Previous studies on the relationship between temporal sense and negative mental health symptoms have focused primarily on healthy college students, overlooking the role of religion. This study sought to examine the impact of religion on college students with sensory impairment and fill a gap in the research on the relationship between temporal sense and negative mental health symptoms in this population. The results were obtained from a cross sectional survey of 540 participants, including 370 hearing-impaired students and 140 visually impaired students. The survey investigated the mediating effect of religion on the relationship between temporal sense and negative mental health symptoms in impaired students. The rates of negative mental health symptoms (depression, anxiety, and stress) detected were 18.9%, 31.1%, and 2.9%, respectively. Students with different types of sensory impairments showed significant differences in their perception of time. The percentages of students with sensory impairments who attended church and practiced religion were 2.0%, 6.0%, and 1.0%, respectively. The results revealed a significant positive correlation between temporal sense and negative mental health symptoms, with religion serving as a mediating factor.